Prototype models of opportunity recognition and the decision to launch a new venture: identifying the basic dimensions - Santos, S. C. (2017)
Purpose – The purpose of this paper is to obtain evidence concerning the basic dimensions included in cognitive prototypes pertaining to opportunity recognition and decision to launch a new venture; identifying the underlying dimensions of both prototypes – the cognitive frameworks current or nascent entrepreneurs employ in performing these important tasks. Design/methodology/approach – The bi-dimensional models were tested in a sample of 284 founder entrepreneurs, using a 48-item questionnaire. It was used as structural equation confirmatory factor analysis to compare fit indices of uni-dimensional second-order and third-order bi-dimensional models of business opportunity and decision to launch a venture. Findings – Results support the bi-dimensional models and offer support that both prototypes include two basic dimensions. For the business opportunity prototype these are viability and distinctiveness while for the decision to launch a new venture, the basic dimensions are feasibility and motivational aspects. Research limitations/implications – These results help to further clarify the nature of the cognitive frameworks individuals use to identify potential opportunities and reach an initial decision about whether to pursue their development. Uncovering the cognitive functioning of opportunity recognition and decision to exploit it, allow individuals to recognize opportunities easier and successfully; and to make more accurate and effective decisions. Practical implications – Knowing the basic dimensions of opportunity and decision-making prototypes contributes to develop effective skills with respect to business opportunity recognition among students enrolled in entrepreneurship programs. These surveys can be used for self-assessment and also for investors, tutors, and entrepreneurship agents in order to help evaluate features of business opportunities and decision to launch a venture. Originality/value – This study embraces a conceptual contribution, proposing a different model of the business opportunity and decision to exploit prototypes, and it extends Baron and Ensley (2006) previous work, to another important step in the entrepreneurial process – the decision to develop an identified opportunity through the launch of a new venture.